Predicting Coping With Self-Regulated Distance Learning in Times of COVID-19: Evidence From a Longitudinal Study - Berger, Fred; Schreiner, Claudia; Hagleitner, Wolfgang; Jesacher-Rößler, Livia; Roßnagl, Susanne; Kraler, Christian (Frontiers in Psychology, 2021)
Due to the COVID-19 pandemic, students worldwide have experienced fundamental changes of their learning. Schools had to shift to distance education as part of the efforts to stop the spread of the virus. Although distance learning undoubtedly bore challenges for all students, we assume that it exacerbated existing educational inequalities and led to disadvantages in particular for students who were already struggling academically and lacking support from family and school. The aim of this paper was to investigate differences in coping with self-regulation in times of distance learning and to examine the possible impact of family, child, and school characteristics on widening the educational gap. The paper draws on data from a two-wave longitudinal study surveying 155 lower secondary school students aged 13 to 14 years from a rural-alpine region in Austria. Data were collected one year before the start of the pandemic and directly after schools had returned to in-class teaching after the first lockdown. Our findings support the notion that distance learning poses a substantial risk for enhancing existing educational disadvantages. They show that out-of-school learning was especially challenging for students with low academic achievement and learning motivation prior to the pandemic because they lack the knowledge, skills, and persistence in task-oriented behavior necessary to generate learning gains through self-regulated remote learning. Furthermore, findings demonstrate that support from parents and teachers fosters students’ capabilities to cope with the self-regulatory demands connected with distance learning. Although the importance of competencies for self-regulated learning became particularly evident in the context of the pandemic, from our findings it can be concluded that, in the future, schools should strengthen their investment in promoting competencies for self-regulated learning. Self-regulation must be recognized as an essential educational skill for academic achievement and life-long learning.